Prophet Muhammd (SAW) The Messenger of Allah - saniyasnainKhan (UAE goodwordbooks, 2024)
"Prophet Muhammad, The Messenger of Allah," by Saniyasnain Khan, is a children's book that introduces the life and teachings of the Prophet Muhammad in a simple and engaging way. The book covers his birth in Mecca, his early life, the beginning of his prophethood, his message of Islam, and the challenges he faced, highlighting his values of honesty, kindness, compassion, forgiveness, and peace
This book is from Islamic stories shelf:C R:1